Personality and intelligence as predictors of creativity - Furnham, A; Bachtiar, V (2008)
Participants completed the Big Five NEO-FFI (Costa and McCrae, 1992) as a personality measure, the Wonderlic Personnel Test (Wonderlic, 1992) as an intelligence measure, and four measures of creativity: Guilford's (1967) unusual uses divergent thinking test; the Biographical Inventory of Creative Behaviours; a self-rated measure of creativity; and the Barron-Welsh Art Scale to measure creative judgement. Extraversion was significantly related to all four measures of creativity. Intelligence failed to add any incremental variance in predicting the creativity scores. Multiple regression indicated that up to 47% of the variance in divergent thinking scores can be accounted for by the Big Five personality traits. Personality correlates to creativity vary as a function of the creativity measure. © 2008 Elsevier Ltd. All rights reserved.